Análise da capacidade funcional em idosos do município de Avaré-SP: fatores associados - Kagawa, Carlos Alexandre; Corrente, José Eduardo (Universidade do Estado do Rio Janeiro, 2015)
Objective: The aim of the present study was to evaluate the influence of quality of life and socio-economic aspects on the functional capacity of elderly residents in the town of Avaré, São Paulo.Methodology: A cross-sectional study of 365 elderly persons living in the urban area of Avaré was performed. A sociodemographic questionnaire, the Flanagan Quality of Life Scale (FQLS), the Katz Activities of Daily Living Scale (ADL) and the Lawton & Brody Instrumental Activities of Daily Living Scale (IADL) were used for data collection.Results: Positive associations were found between the ADL and IADL of elderly persons who reported having a poor quality of life. The same was found for certain aspects of quality of life as measured by the FQLS. Of the 15 items of this scale, four influenced ADL: health, self-awareness, work and leisure, while seven influenced IADL: self-awareness, health, work, community involvement, relations with friends, socializing (making friends) and learning through courses and lectures.Conclusion: Elderly people with a good quality of life and more elevated socio-economic status are less functionally dependent, and there are specific aspects of quality of life that most influence functional disability in the performance of ADL and IADL.

Objetivo:Este estudo objetivou avaliar a influência da qualidade de vida e aspectos socioeconômicos na capacidade funcional em idosos moradores do município de Avaré-SP.Métodos:Trata-se de estudo transversal. A amostra foi composta por 365 idosos, moradores da zona urbana de Avaré-SP. Os instrumentos utilizados foram: questionário sociodemográfico, escala de Qualidade de Vida de Flanagan (EQVF), escala de Atividades Básicas da Vida Diária (ABVD) de Katz e Atividades Instrumentais da Vida Diária (AIVD) de Lawnton & Brody.Resultados:Foram encontradas associações positivas entre ABVD e AIVD para os idosos que referiram não ter qualidade de vida. O mesmo ocorreu com alguns aspectos da qualidade de vida, medida pela EQVF; entre os 15 itens, quatro influenciaram as ABVDs: saúde, autoconhecimento, trabalho e lazer. Para as AIVDs, sete itens, entre os 15, influenciaram mais a capacidade funcional: autoconhecimento, saúde, trabalho, participação na comunidade, reunir com os amigos, socialização (fazer amigos) e aprendizagem em cursos e palestras.Conclusão:Idosos com boa qualidade de vida e com condição socioeconômica melhor apresentam menos dependência funcional, e há aspectos específicos da qualidade de vida que influenciam mais a incapacidade funcional, tanto para as ABVDs como para as AIVDs.
Analysis of elderly functional capacity in the municipality of Avaré, São Paulo: associated factors
Keywords: Elderly; Functional Capacity; Quality of Life; Idoso; Capacidade Funcional; Qualidade de Vida